(untitled) (Brazilian Journal of Behavioral and Cognitive Therapy, 2004)
The obsessive-compulsive disorders (OCD) and the obsessive-compulsive personality disorders (OCPD) have shown, along the history, conceptual similarities that have confused therapists and scientists’ diagnosis. In part, the ambiguity probably appears as a result of poor use of the methods in the diagnostic process and due to the insufficient professional training. Mistakes also happen due to the existence of a considerable similarity between the behavioral phenomena. As this is a very serious issue, a deeper conceptual analysis is warranted. The goal established in this paper was to analyze the case of a client attended during the academic training. From the analysis of the case, a hypothesis was raised about the similarities between the operant variables of both disorders. It was concluded that phenomenological similarity occurs due to the similarity in the controlling variables and not because of the behavioral topographies.